Pengaruh Satu dan Dua Sudu Terhadap Kinerja Turbin Archimedes Screw - Ronaldo Siahaan; Dianna Ratnawati; zainuri anwar; Hasnul Azwan (Universitas Sarjanawiyata Tamansiswa, 2023)
One of the parameters that affect turbine performance is the amount and shape of the turbine blades. This study aims to determine the effect of the amount of Archimedes screw turbine blades on turbine performance. The type of turbine used in this study is the Archimedes turbine with single and double screw balde. The turbine test was carried out in the Puri Kedaton river, Pematang Gajah village, with a flow rate entering the turbine of 0.043 m3/s. The shaft load received by the turbine is varied, namely 30 kg, 40 kg, 50 kg and the tilt of the turbine is installed 30°. The test results show that the double screw turbine type produces 518 Watt turbine power with the highest efficiency of 80,5%.